6. MF59 ASSURANCE 2: A Real-world Study to Estimate the Relative Vaccine Effectiveness of Adjuvanted Trivalent Influenza Vaccine Compared to Egg-based Trivalent High-dose Among U.S. Older Adults During 2018–19 Influenza Season. (31st December 2020) - Pelton, Stephen I; Postma, Maarten; Divino, Victoria; Shah, Drishti; Mould-Quevedo, Joaquin F; DeKoven, Mitchell; Krishnarajah, Girishanthy
Abstract: Background: In the 2018–19 influenza season, influenza resulted in almost 280, 000 hospitalizations and over 25, 000 deaths in U.S. adults > 65 years. This study aimed to evaluate the relative vaccine effectiveness (rVE) of adjuvant trivalent influenza vaccine (aTIV) compared to high-dose trivalent influenza vaccine (TIV-HD), against influenza-related hospitalizations/emergency room (ER) visits, office visits and hospitalization/ER visit for cardio-respiratory disease (CRD) among older adults for the 2018–19 flu season. Methods: A retrospective cohort analysis of older adults ( > 65 years) was conducted using professional fee, prescription claims and hospital charge master data in the U.S. Baseline characteristics included age, gender, payer type, region, Charlson Comorbidity Index (CCI), comorbidities, indicators of frail health status, and pre-index hospitalization rates. Adjusted analyses were conducted through inverse probability of treatment weighting (IPTW) to control for selection bias. Poisson regression was used to estimate the adjusted pairwise rVE against influenza-related hospitalizations/ER visits and office visits and any hospitalization/ER visit for CRD (based on diagnoses codes). An unrelated outcome, urinary tract infection (UTI) hospitalization, was assessed. Results: During 2018–19 flu season, following IPTW analyses, 561, 315 recipients of aTIV and 1, 672, 779 of TIV-HD were identified. After IPTW adjustment and Poisson regression, aTIV was more effective in reducing influenza-related office visits compared to TIV-HD (6.6%; 95% CI: 2.8%-10.3%). aTIV was statistically comparable to TIV-HD (2.0%; 95% CI: -3.7%-7.3%) for prevention of influenza-related hospitalizations/ER visits but more effective than TIV-HD (2.6%; 95% CI: 2.0%-3.2%) in reducing hospitalizations/ER visits for CRD. No treatment effect was identified for control condition (UTI hospitalization). Conclusion: In adjusted analyses, aTIV reduced influenza-related office visits and CRD hospitalizations/ER visits compared to TIV-HD. aTIV and TIV-HD demonstrated comparable reductions in influenza-related hospitalizations/ER visits. Disclosures: Stephen I. Pelton, MD, Merck vaccine (Consultant, Grant/Research Support)Pfizer (Consultant, Grant/Research Support)Sanofi Pasteur (Consultant, Other Financial or Material Support, DSMB)Seqirus Vaccine Ltd. (Consultant) Maarten Postma, Dr., IQVIA (Consultant) Victoria Divino, PhD, Seiqrus Vaccines Ltd. (Consultant) Drishti Shah, PhD, Seqirus Vaccines Ltd. (Consultant) Joaquin F. Mould-Quevedo, PhD, Seqirus Vaccines Ltd. (Employee, Shareholder) Mitchell DeKoven, PhD, Seqirus Vaccines Ltd. (Consultant) Girishanthy Krishnarajah, PhD, Seqirus Vaccines Ltd. (Employee, Shareholder)